The Role Of Sustainable Transportation In Shaping Metropolitan Mobility: A Survey Analysis In Esenyurt, Istanbul - Narmin ABDULMAJEED (Genius Journals, 2025)
Sustainable transportation plays a key role in addressing environmental issues and influencing urban mobility. The study's focus is on Esenyurt, a rapidly growing neighborhood in Istanbul where sustainable transportation is needed. Through a survey of traveler behavior and public opinion, the research determines the main problems, which include; inadequate public transportation, a heavy reliance on private vehicles, inadequate infrastructure for cyclists and pedestrians, and a lack of places to charge electric cars. The paper suggests Esenyurt to adopt approaches used in cities like Copenhagen, Zurich, and Amsterdam based on international best strategies towards sustainability. For instance, Copenhagen's bicycle lanes, Zurich's extensive public transportation and car parking regulations, and Amsterdam's car-free zones and reducing parking-lots have all helped to reduce traffic and air pollution. Esenyurt needs bike lanes, congestion fees, better public transportation like rail ways, and car-free zone in order to accomplish the same approach. For cities to become clean, livable, and more sustainable transportation system, all may be achieved through policy adjustments, infrastructural investment, and behavioral change.
Keywords: Car Dependency; Sustainable Transportation; peoples’ perceptions